Evaluation of time and resources required for professional dental cleaning in nursing home residents. (3rd January 2019) - Barbe, Anna Greta; Kottmann, Hannah Elisa; Müller, Dirk; Simic, Dusan; Derman, Sonja Henny Maria; Wicht, Michael Jochen; Noack, Michael Johannes
Abstract: Aim: We aimed to describe time requirements and costs associated with professional dental cleaning (PDC) performed by a dental nurse in one German nursing home, and to reveal potential differences in required time for demented versus nondemented and mobile versus immobile residents. Methods and results: We performed a retrospective, cross‐sectional analysis of treatment time and costs, including a transparent, easily adaptable path of action that allows implementation of PDC in nursing homes. Total mean (±SD) treatment time for one session per resident was documented, including differences in demented and immobile residents, and projected treatment costs (€/ ) per resident. We found no differences in required time for one PDC (37 ± 11 minutes) in residents with or without dementia ( P = 0.803) or, immobile versus mobile residents ( P = 0.396). Mean projected treatment costs of PDC were €14.98/ 17.07 per resident per cleaning session, resulting in total costs of €13.5 million (15.4 million). Conclusion: Cognitive status and mobility does not affect the mean time required to perform PDC by a dental nurse in nursing home residents. Main cost factor is working time of dental staff; consumable supplies have less impact. Our data may stimulate to include PDC as initial step toward implementation of long‐term oral hygiene strategies.